Symbolic Narratives in Graphic Design: Semiotic Perspectives on Advertising Visuals - Ayça Yılmaz; Bilal Kır (Bodrum Journal of Art and Design)
This study examines how consumer culture is reproduced through advertising visuals in the context of graphic design. Three different advertisements were selected, and the graphic design elements used in these visuals (such as color, composition, and symbols) were analyzed in terms of their impact on consumer perception. Employing the semiotic analysis method, the study reveals that advertising visuals are not merely aesthetic tools but also carriers of ideological and social meanings. The findings indicate that graphic design elements effectively convey the ideological messages of consumer culture and establish profound symbolic connections between brands and consumers. Additionally, the role of graphic design has become more prominent in the digital era, evolving into an interactive and multi-layered structure within modern consumer culture. This study underscores the critical function of graphic design as a communication tool that not only creates visual aesthetics but also shapes social values and consumer behaviors. In conclusion, advertising visuals are evaluated as strategic tools in the reproduction of consumer culture, contributing to theoretical and applied studies in this field.